Diopathic Granulomatous Mastitis: A Multifaced Approach - Ramalingam, Lavanya; Kumar T, Dinesh (Journal of Neonatal Surgery, 2025)
Idiopathic granulomatous mastitis remains one the most mismanaged benign breast disease due to the difficulty in its diagnosis. As it closely resembles breast cancer as well as tubercular and pyogenic breast abscess, surgeons often excise the lesion or drain the abscess as soon as possible. This leads to an increase in recurrences and causes significant disfigurement. Patients are often distressed, in chronic pain and have massive financial burdens due to repetitive surgical procedures, given the waxing and waning course of this disease. Hence, a standardized multidisciplinary approach is required to effectively treat the disease with minimal relapses and recurrences..